Separations for biotechnology 2 - International Symposium on Separations for Biotechnology (2nd : 1990 : University of Reading); Pyle, D. L.; Society of Chemical Industry (Great Britain). Biotechnology Group; Society of Chemical Industry (Great Britain). Solvent Extraction Group (London : Published for SCI by Elsevier, 1990)
50